2021
DOI: 10.1089/chi.2020.0174
|View full text |Cite|
|
Sign up to set email alerts
|

Modifiable Early Childhood Risk Factors for Obesity at Age Four Years

Abstract: Background: Childhood obesity is associated with an increased risk of adult obesity and related chronic disease. Our aim was to identify modifiable exposures that are independently associated with obesity in the preschool age group.Methods: A prospective cohort study of 5734 children in New Zealand with anthropometric measurements was completed at age 4.5 years. The modifiable exposures of interest, measured at age 9 months and 2 years, were: food security during infancy; and, at age 2 years, screen time; slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Regarding the first hypothesis (H1), no significant relationship was found between dietary factors and obesity, like other studies [ 2 , 49 , 56 , 85 ]. The results were found in the present study probably because the study sample belonged to a rural area, in which young people maintain good adherence to the Mediterranean diet, which is rich in fruits, vegetables, and fish [ 86 ].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Regarding the first hypothesis (H1), no significant relationship was found between dietary factors and obesity, like other studies [ 2 , 49 , 56 , 85 ]. The results were found in the present study probably because the study sample belonged to a rural area, in which young people maintain good adherence to the Mediterranean diet, which is rich in fruits, vegetables, and fish [ 86 ].…”
Section: Discussionmentioning
confidence: 61%
“…The relationship between lifestyle habits and the development of excess weight in adolescence is a widely studied topic [ 3 , 49 , 51 , 55 ]. However, the current study used the novel partial least squares structural equation modeling (PLS-SEM) method, which is widely used in other fields and whose results allow the hypotheses to be contrasted and actions in certain areas susceptible to improvement to be proposed [ 20 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inadequate sleeping has a greater impact on obesity in 9–13 years old boys than in 4–8 years old boys ( 14 ). The cumulative population attributable fraction (PAF) for childhood obesity was 42.9% in a cohort study in New Zealand, as if the excessive screen time and several other related factors were eliminated ( 15 ). Furthermore, a study found that not participating in sports' teams (PAF, 16.57%; 95% CI, 15.30–17.84%) had the biggest influence on the rate of obesity in American high school students, followed by watching TV and playing computer games ( 16 ).…”
Section: Introductionmentioning
confidence: 99%